Immunotherapy augments the effect of 5-azacytidine on HPV16-associated tumours with different MHC class I-expression status - Símová, J; Polláková, V; Indrová, M; Mikyšková, R; Bieblová, J; Stěpánek, I; Bubeník, J; Reiniš, M (British journal of cancer, 2011)
BACKGROUND: Epigenetic mechanisms have important roles in the tumour escape from immune responses, such as in MHC class I downregulation or altered expression of other components involved in antigen presentation. Chemotherapy with DNA methyltransferase inhibitors (DNMTi) can thus influence the tumour cell interactions with the immune system and their sensitivity to immunotherapy. METHODS: We evaluated the therapeutic effects of the DNMTi 5-azacytidine (5AC) against experimental MHC class I-deficient and -positive tumours. The 5AC therapy was combined with immunotherapy, using a murine model for HPV16-associated tumours. RESULTS: We have demonstrated 5AC additive effects against MHC class I-positive and -deficient tumours when combined with unmethylated CpG oligodeoxynucleotides or with IL-12-producing cellular vaccine. The efficacy of the combined chemoimmunotherapy against originally MHC class I-deficient tumours was partially dependent on the CD8(+)-mediated immune responses. Increased cell surface expression of MHC class I cell molecules, associated with upregulation of the antigen-presenting machinery-related genes, as well as of genes encoding selected components of the IFNγ-signalling pathway in tumours explanted from 5AC-treated animals, were observed. CONCLUSION: Our data suggest that chemotherapy of MHC class I-deficient tumours with 5AC combined with immunotherapy is an attractive setting in the treatment of MHC class I-deficient tumours.
Keywords: kvantitativní polymerázová řetězová reakce; Human papillomavirus 16; protinádorové antimetabolity; Histocompatibility Antigens Class I; experimentální nádory; sekvence nukleotidů; azacytidin; Methylation; myši inbrední C57BL; zvířata; Animals; Neoplasms, Experimental; Male; myši; Real-Time Polymerase Chain Reaction; Azacitidine; ELISA; imunoterapie; mužské pohlaví; DNA Primers; Base Sequence; Mice; Antimetabolites, Antineoplastic; Immunotherapy; lidský papilomavirus 16; MHC antigeny I. třídy; metylace; Enzyme-Linked Immunosorbent Assay; DNA primery; Mice, Inbred C57BL